Chromatographic profile of xanthones and flavonoids in the anti-dengue extracts of Fridericia samydoides (Cham.) L.G. Lohmann (Bignoniaceae) - Juliane Morais da Fonseca; Adriana Cotta Cardoso Reis; Guilherme Rocha Pereira; Hélia Maria Marques de Moura; José Dias Souza Filho; Breno de Mello Silva; Geraldo Célio Brandão (Universidade de São Paulo, 2022)
Abstract The flavonoids and xanthones present in the ethanol extracts of leaves and stems of Fridericia samydoides showed that anti-dengue activities in vitro were investigated qualitatively by liquid chromatography-ultraviolet-mass spectrometry in series. Nineteen flavones and fifteen xanthones were detected and characterized on the basis of their fragmentation pattern in the positive and negative ion mode tandem mass spectrometry spectra and ultraviolet bands. Acacetin, chrysin, vitexin, isovitexin, orientin, isoorientin, mangiferin, 2'-O-trans-caffeoylmangiferin, 2'-O-trans-coumaroylmangiferin and 2'-O-trans-cinnamoylmangiferin were identified by comparison with authentic samples. The other compounds detected were tentatively assigned by analysis of the spectral data and by comparison with literature reports. In addition, it performed the fractionation of the leaves extract leading to the isolation of mangiferin, isovitexin and isoorientin. All extracts and isolated compounds inhibited the Dengue virus replication cycle with EC50 less than 25.0 µg/mL for extracts and 272.5, 85.6 and 79.3 µg/mL for mangiferin, isovitexin and isoorientin, respectively.